Aircraft Landing Scheduling Based on Unavailability of Runway Constraint Through a Time Segment Heuristic Method - Amir Mirzadeh Phirouzabadi; M. Aminnayeri; M. Mahmoudian (International Journal of Informatics and Communication Technology (IJ-ICT), 2013)
Noting the problem of increasing airports congestion, it is crucial to obtain a practical and efficient scheduling for departure and landing. The problem of deciding how to land an aircraft on the airport involves assigning each aircraft to an appropriate runway, computing a landing sequence for each runway and scheduling the landing time for each aircraft. The objective was to achieve effective runway use. In this paper, a multiple runway case of the static Aircraft Landing Problem was considered. It was assumed that one of the runways is not available. A mixed integer formulation approach was proposed to deal with the problem. The approach of solving this problem was breaking down the main problem into several sub problems. To validate the model, eight test problems were extracted from the OR-Library and discussions made on their solutions.DOI: http://dx.doi.org/10.11591/ij-ict.v2i3.5284